2014
DOI: 10.1155/2014/616018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Blood Type, Functional Polymorphism (T-1676C) of theCOX-1Gene Promoter and Clinical Factors on the Development of Peptic Ulcer during Cardiovascular Prophylaxis with Low-Dose Aspirin

Abstract: Aims. To investigate the impact of blood type, functional polymorphism (T-1676C) of the COX-1 gene promoter, and clinical factors on the development of peptic ulcer during cardiovascular prophylaxis with low-dose aspirin. Methods. In a case-control study including 111 low-dose aspirin users with peptic ulcers and 109 controls (asymptomatic aspirin users), the polymorphism (T-1676C) of the COX-1 gene promoter was genotyped, and blood type, H pylori status, and clinical factors were assessed. Results. Univariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(38 reference statements)
0
1
1
1
Order By: Relevance
“…Our study proved the role of infection in mucosal damage in aspirin consumers. In our study, more than 50% of patients with ulcer were H. pylori positive, a percentage higher than in the majority of similarly published papers [20]. Concurrent use of NSAIDs, frequently with no medical prescriptions (data not showed), was a significant risk factor for ulcer, in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…Our study proved the role of infection in mucosal damage in aspirin consumers. In our study, more than 50% of patients with ulcer were H. pylori positive, a percentage higher than in the majority of similarly published papers [20]. Concurrent use of NSAIDs, frequently with no medical prescriptions (data not showed), was a significant risk factor for ulcer, in our study.…”
Section: Discussioncontrasting
confidence: 56%
“…22 At present, the common mutation sites in the 5 terminal non-coding regions of the COX-1 gene are A-842G, 1676 T-C, G-1498A, A1201G, T1794C, G-10006A, A-918G and A-807G. [23][24][25][26][27][28] The -842 A-G allele mutation was present in 60% of aspirin-resistant patients, while only 17% of non-aspirin-resistant patients had the mutation at the above site, suggesting that the A-842G allele mutation is closely related to aspirin resistance. 25 It was further found that the polymorphic changes at this gene locus could significantly increase the expression level of thrombin B2 and stimulate platelet aggregation, leading to an increased risk of thrombosis.…”
Section: Cox Genesmentioning
confidence: 99%
“…Так, применение НПВП или аспирина с селективными ингибиторами обратного захвата серотонина, кортикостероидами, антагонистами альдостерона или антикоагулянтами существенно увеличивает риск развития желудочно-кишечного кровотечения [19]. Результаты некоторых исследований показали связь использования аспирина с повышенным риском язвенной болезни у пациентов с генетическими полиморфизмами (T-1676C, PSCA rs2 294 008), но клиническая значимость этих исследований до конца не ясна [20].…”
Section: рис 2 гастритоподобный вариант неходжкинской лимфомы желудunclassified